Peningkatan Hasil Belajar pada Pembelajaran Matematika dengan Model Problem Based Learning Kelas IV SD - Vanny Yuniawardani; Mawardi Mawardi (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2018)
The purpose of research to determine the results of learning mathematics using Problem Based Learning model in Class IV SD N Gendongan 03. Type of research that is a Classroom Action Research or PTK or Classroom Action Research. Class Action Plan (PTK) is a research action (action research) that compiled a group of people, which then researchers set action to overcome them. This research was conducted on April-May 2018 at 4th grade students of SDN Gendongan 03. The result of this research was proved by the improvement of the initial condition of the completeness of learning condition as much as 24 students (66,7%) increase in cycle I 28 students (77,8%) and in the second cycle increased to 31 students (86.1%). It can be concluded that the research was successful.